Research progress and applications of memristor emulator circuits. (March 2023) - Lin, Rubin; Shi, Ge; Qiao, Fei; Wang, Chenyu; Wu, Shien
Abstract: From the perspective of circuit theoretical integrity, it can be predicted that there is a fourth passive basic element, and this missing circuit element is named as memristor. Memristor is a two-terminal device whose value depends on the history of the magnetic flux or charge flowing through it. As a fourth basic element, it is considered a promising device in many analog and digital applications. However, the cost and difficulty of making nanodevices limit the commercialization of memristor. To better study memristor, researchers have proposed the use of circuits composed of different components to simulate memristor characteristics, also known as memristor emulator circuits. This paper presents the current research status of memristor emulator circuits, and analyses the design ideas, circuit composition, advantages and disadvantages of emulator circuits implemented by different schemes, then introduces the application of some emulators in real circuits.